2020
DOI: 10.1002/lol2.10147
|View full text |Cite
|
Sign up to set email alerts
|

Snowpack determines relative importance of climate factors driving summer lake warming

Abstract: Lake thermal regimes are frequently decoupled from rising air temperature trends in their watersheds because interactions among climate factors and local features affect net heat gain or loss. Although snowpack has been empirically linked to temperature and warming rates in mountain lakes, the mechanisms governing this relationship remain unclear and untested, despite predicted declines in mountain snow across the world. We quantified how snowpack and ice cover regulate lake warming in summer primarily by cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Decreases in snowfall usually are greatest near the low-elevation margin of the snowpack and cause reductions in surface albedo and increases in absorbed solar radiation, further leading to elevation-dependent amplification of warming (Minder et al, 2018). In snow-dependent mountain lakes, the amount of spring snowmelt, ice-off timing, and duration of ice cover is strongly tied to the evolution of physical processes such as thermal stratification and mixing (Flaim et al, 2019;Preston et al, 2016;Sadro et al, 2019;Smits et al, 2020;Zhang et al, 2014). Furthermore, topography, especially as it determines the amount and timing of solar radiation impinging on a lake, can also be a major factor affecting the physics and biology of mountain lakes (Flaim et al, 2010(Flaim et al, , 2019Ptak et al, 2018;Sadro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in snowfall usually are greatest near the low-elevation margin of the snowpack and cause reductions in surface albedo and increases in absorbed solar radiation, further leading to elevation-dependent amplification of warming (Minder et al, 2018). In snow-dependent mountain lakes, the amount of spring snowmelt, ice-off timing, and duration of ice cover is strongly tied to the evolution of physical processes such as thermal stratification and mixing (Flaim et al, 2019;Preston et al, 2016;Sadro et al, 2019;Smits et al, 2020;Zhang et al, 2014). Furthermore, topography, especially as it determines the amount and timing of solar radiation impinging on a lake, can also be a major factor affecting the physics and biology of mountain lakes (Flaim et al, 2010(Flaim et al, , 2019Ptak et al, 2018;Sadro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…J S had a robust relationship with spring mean air temperature, reflecting other models that describe the negative influence of this variable (Crossman et al 2016) Smits et al 2020). Changes in wind speed can have large effects on lake stratification dynamics, and outweigh the long-term effects of air temperature (Woolway et al 2017) and change the likelihood of stratification in small lakes (Martinsen et al 2019).…”
Section: Onset Of Lake Stratification (J S )mentioning
confidence: 70%
“…S4) corresponding to the date of peak land surface air temperature, described by (Gorham 1964), thus, they take longer to reach their maximum temperature leading to higher J M values, as represented by the positive effect of ln(area) on J M . We expected to see a positive relationship between J M and elevation, as lakes at relatively high elevations on a regional scale have been shown to reach their peak summer surface water temperatures at later dates than lower elevation lakes (Livingstone et al 2005), possibly due to delayed ice-off and increased snowpack at higher elevations (Smits et al 2020). We found that adding an elevation term improved the model, but the model coefficient had a negative sign which opposed the potential mechanistic relationship explained above, so we removed the elevation term from the ETM.…”
Section: Day Of Maximum Surface Water Temperature (J M )mentioning
confidence: 99%
See 1 more Smart Citation
“…In stratified lakes, epilimnetic temperatures may decrease because of colder water from the hypolimnion mixing into the epilimnion (Znachor et al 2008; Umaña‐Villalobos 2014), upwelling, internal waves breaking at the shore, or heat flux at the lake surface altered by wind, rain, or changes in air temperature (e.g., Andreas et al 1995; Kasprzak et al 2017; Rooney et al 2018). However, the extent of temperature change from storm events also depends on a variety of environmental and lake characteristics (Padisák et al 1988; Kuha et al 2016; Andersen et al 2020), such as the frequency of storm events (Smits et al 2020), internal seiche dynamics (Woolway et al, 2018), lake mixing regime (Jennings et al 2012; Kuha et al 2016), and the ratio of the watershed area to the lake surface area (WA:SA) (Jennings et al 2012; Klug et al 2012). Therefore, what constitutes a storm and how storms may affect lake processes are highly variable, making comparisons across waterbodies difficult (Stockwell et al 2020).…”
Section: Introductionmentioning
confidence: 99%